THE EFFECT OF FINANCIAL LITERATURE ON FINANCIAL INCLUSION MEDIATED BY FINANCIAL TECHNOLOGY - Azizah, Lulu'atul; Azizah, Nur; Yuliana, Indah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
The study aims to ascertain whether the financial literacy factor among students can influence financial inclusion, as well as the role of financial technology in facilitating activities in the financial services sector. By using the slovin method, 82 respondents were obtained as samples from the total population of 483 students of FE UIN Malang Class 2018. Data analysis in the study This uses the Partial Least approach Square or PLS. Based on hypothesis testing, the results obtained are 1) Financial Literacy has a significant positive effect on Financial Inclusion; 2) Financial Literacy has a significant positive effect on Financial Technology; 3) Financial Technology has a significant positive effect on Financial Inclusion; 4) Financial Technology is capable mediates the relationship between Financial Literacy and Financial Inclusion.